Strategies for More Effective Demonstrations: Editor: Ferman Konukman. Issue 4 (3rd May 2016) - Ryan, Stu; Maina, Michael; Mokgwathi, Martin
Abstract : This article presents a few examples of effective demonstration strategies that will help physical education teachers convey important skill information to their students.